Forecasting Recessions in Real Time - Knut Are Aastveit; Anne Sofie Jore; Francesco Ravazzolo (Norges Bank, 2014)
We review several methods to define and forecast classical business cycle turning points in Norway. In the paper we compare the Bry - Boschan rule (BB) with a Markov Switching model (MS), using alternative vintages of Norwegian Gross Domestic Product (GDP) as the business cycle indicator. The timing of business cycles depends on the vintage and the method used. BB provides the most reasonable definition of business cycles. The forecasting exercise, where the models are augmented with surveys or financial indicators, respectively, leads to the conclusion that the BB rule applied to density forecasts of GDP augmented with either the consumer confidence index or a financial conditions index provides the most timely predictions of peaks. For troughs, augmenting with surveys or financial indicators does not increase forecastability.
hdl:11250/2495983
Keywords: C32; C52; C53; E37; E52; 330; forecast densities; turning points; real-time data